Why is Chemistry Education? Exploring the Motivation of Student Choices - Rahmawan, Setia; Rian Nurhadi, Atep; Mursalin, Enggal; Darwis, Rahmiati (Indonesian Journal of Science and Education, 2024)
Learning motivation is critical to educational success, influencing students' engagement, persistence, and overall performance. Despite its importance, motivation determines students' choices for future careers and struggles in participating in learning activities. The aim was to characterize students' chemistry learning motivation in detail using the Academic Motivation Scale - Chemistry (AMS-Chemistry). This study employs a descriptive qualitative research design. The qualitative approach allows an in-depth exploration of personal experiences and perceptions of learning motivation in chemistry education. The AMS-Chemistry instrument consists of 28 statement items that measure aspects of amotivation, three types of extrinsic motivation, and three types of intrinsic motivation. The results show that the motivation profile to learn Chemistry in Chemistry Education students using the AMS-Chemistry instrument on the amotivation subscale tends to disagree (55,46%). On intrinsic motivation, the to know subscale tends to agree (65,80%) strongly, the to accomplish subscale has a high score on strongly agree (48,85%) responses, and the to experience subscale tends to respond strongly agree (35,34%). Extrinsic motivation includes the external regulation subscale tending to strongly agree (55,17%) and the introjected regulation subscale having a high score on strongly agree (62,36%) responses. The identified regulation subscale has a strongly agree (68,97%) response tendency.